The problem of tissue and organ transplantation in the light of the dogma of world religions - Chatys, Klaudia Magdalena; Pawłowski, Piotr; Widłak, Karolina; Ziętara, Karolina; Kościołek, Aneta; Adamska–Kuźmicka, Iwona; Jakubowska, Klaudia (Journal of Education, Health and Sport, 2022)
Background: Transplantation affects almost everyone, often affecting many almost directly, whether as donor or recipient. The presence of an incurable disease, failure, or irreversible damage to a particular organ leads the patient and his or her treatment team to seek effective life-saving methods, including the possibility of tissue or organ transplantation. The development of the field of transplantology has enabled many patients to continue living. Paradoxically, the death of one person can offer life to another. Aim of the study: To analyse the attitude towards transplantation about the dogmas of the main world religions. Material and method: A non-systematic review of Polish and English-language scientific literature was carried out according to keywords: transplantation, transplantology, religion, denomination, and attitude. No time or methodological limitation (quantitative, qualitative, etc.) was indicated to qualify publications for review. The following databases were searched: PubMed, Scopus, Web of Science, and Google Scholar. Results and conclusions: The Catholic Church, the Protestant Church, the Orthodox Church, Islam, Judaism, and Jehovah’s Witnesses do not directly oppose organ transplantation, although some denominations place certain conditions on the acceptance of transplantation. Gypsies, followers of Confucianism and Shintoism are opposed to performing transplants from deceased persons. The religions presented do not promote among their followers either to be donors or recipients of transplants. The level of transplantation worldwide varies. So far, there is a perception that undergoing this procedure is against one’s religion and tradition.